Respuesta agronómica y productiva de dos híbridos de brócoli (Brassica oleracea), a diferentes dosis de fertilización nitrogenada en la localidad de Guapoloma, cantón San Miguel, provincia Bolívar - Moyano Velasco, Oscar Ulbio (2019)
In our country the provinces of Cotopaxi, Pichincha, and Imbabura are the main producers of Broccoli, in the Bolivar province their production is transiently found mainly in family gardens. This research was carried out in the Guapoloma precinct of the San Miguel province of Bolívar, the date of the transplant was on June 25, 2018. The objectives that were proposed were: i) To evaluate the agronomic and morphological characteristics of the hybrids. ii) Determine the effect of the three doses of nitrogen fertilization on the broccoli culture. iii) Perform an Economic Analysis of Partial Budget (AEPP) and the Marginal Rate of Return (TMR). A randomized complete block design (DBCA) was used in a 2x4 factorial arrangement with 3 repetitions obtaining 8 treatments. Factor A corresponded to hybrids (Tamer and Avenger) and factor B to nitrogen fertilization doses. A combined analysis of variance was used to determine Tukey tests at 5% to compare averages of factor A and interaction of factors A x B when the Fisher is significant, main effect of hybrids (Factor A), polynomial trend test for N levels, correlation analysis and linear regression, economic analysis of partial budget and calculation of the Marginal Rate of Return. The most important variables that contributed to increase the yield were: Plant Height, Number of Sheets, Weight in kg / plot. There was a highly significant effect on yield, this is due to the different genetic characteristics of the hybrids, and the edaphoclimatic conditions of the sector. The best performance was that of T8 (Hybrid Avenger with 120 Kg / Ha of Nitrogen) with an average of 12403 Kg / Ha. Finally, this research gave us a new alternative for agricultural production in the area, thus improving the productive matrix in the Bolívar province.